1996
DOI: 10.1172/jci118658
|View full text |Cite
|
Sign up to set email alerts
|

Chymase in exocytosed rat mast cell granules effectively proteolyzes apolipoprotein AI-containing lipoproteins, so reducing the cholesterol efflux-inducing ability of serum and aortic intimal fluid.

Abstract: Degranulated mast cells are present in human fatty streaks. Chymase in granules released from degranulated rat serosal mast cells, i.e., in granule remnants, proteolyzes human high density lipoprotein 3 (HDL 3 ), and so reduces its ability to induce cholesterol efflux from macrophage foam cells in vitro. In this study we found that remnant chymase, by proteolyzing human serum and human aortic intimal fluid, prevents these two physiologic fluids from effectively inducing cholesterol efflux from cultured macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 51 publications
4
55
1
3
Order By: Relevance
“…2). This accords with our previous findings that exposure of the LpA-I-containing particles present in HDL 3 and in plasma to a minimal degree of proteolysis by the neutral protease chymase from exocytosed rat mast cell granules or from human skin results in reduced high affinity efflux of cholesterol from macrophage foam cells (15,16). Interestingly, Mendez and Oram (49) have shown that mild trypsin treatment, by proteolyzing a minor trypsin-labile fraction of HDL, almost completely abolished apolipoprotein-mediated cholesterol removal.…”
Section: Fig 6 Proteolytic Degradation Of Hdlsupporting
confidence: 93%
See 2 more Smart Citations
“…2). This accords with our previous findings that exposure of the LpA-I-containing particles present in HDL 3 and in plasma to a minimal degree of proteolysis by the neutral protease chymase from exocytosed rat mast cell granules or from human skin results in reduced high affinity efflux of cholesterol from macrophage foam cells (15,16). Interestingly, Mendez and Oram (49) have shown that mild trypsin treatment, by proteolyzing a minor trypsin-labile fraction of HDL, almost completely abolished apolipoprotein-mediated cholesterol removal.…”
Section: Fig 6 Proteolytic Degradation Of Hdlsupporting
confidence: 93%
“…Cells-Human monocytes were separated from buffy coat cells, allowed to differentiate to macrophages, and loaded with cholesterol, as described before (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The present study was directed toward understanding the mechanisms underlying the blocking effect of chymase on the cholesterol efflux promoted by HDL 3 as previously described. 13,32 For this purpose, we investigated the effect of mast cell granule remnants on the small subpopulations of HDL containing apoAs (pre␤ 1 LpA1, LpA4 -1, and LpA4 -2), which play a role as early cholesterol acceptors from cells. Specifically, we determined whether proteolysis of pre␤ 1 LpA1 would be responsible for the previously observed inhibitory effect of mast cell chymase on the high affinity component of cholesterol efflux from macrophage foam cells.…”
mentioning
confidence: 99%
“…Specifically, we determined whether proteolysis of pre␤ 1 LpA1 would be responsible for the previously observed inhibitory effect of mast cell chymase on the high affinity component of cholesterol efflux from macrophage foam cells. 32 …”
mentioning
confidence: 99%